Pons-Sanz, Sara M. 2013: The Lexical Eff ects of Anglo-Scandinavian Linguistic Contact on Old English - Pascual, Rafael J. (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen